Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation. - Tuysuz, Beyhan; Pehlivan, Davut; Özkök, Ahmet; Jhangiani, Shalini; Yalcinkaya, Cengiz; Zeybek, Çiğdem Aktuğlu; Muzny, Donna Marie; Lupski, James R; Gibbs, Richard; Jaeken, Jaak (JIMD Rep, 2016)
We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous nonsense mutation c.320G>A; p.Trp107X in SRD5A3. Epilepsy and glaucoma have been reported only once in the 19 described SRD5A3-congenital glycosylation defect patients, and corneal clouding not at all.